2019
DOI: 10.1111/jsr.12838
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐individual stability of NREM sleep quantitative EEG measures in obstructive sleep apnea

Abstract: Electroencephalography is collected routinely during clinical polysomnography, but is often utilised to simply determine sleep time to calculate apnea–hypopnea indices. Quantitative analysis of these data (quantitative electroencephalogram) may provide trait‐like information to predict patient vulnerability to sleepiness. Measurements of trait‐like characteristics need to have high test–retest reliability. We aimed to investigate the intra‐individual stability of slow‐wave (delta power) and spindle frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…Numerous studies have reported a relationship between EEG power and daytime sleepiness. 10 , 27 , 28 This study also found a correlation between the ESS score and the average absolute power of delta and DAR ( P < 0.05). This confirmed that slow frequency EEG activity may be a clinical biomarker of daytime sleepiness.…”
Section: Discussionsupporting
confidence: 64%
“…Numerous studies have reported a relationship between EEG power and daytime sleepiness. 10 , 27 , 28 This study also found a correlation between the ESS score and the average absolute power of delta and DAR ( P < 0.05). This confirmed that slow frequency EEG activity may be a clinical biomarker of daytime sleepiness.…”
Section: Discussionsupporting
confidence: 64%
“…We also acknowledge there is night-to-night variability in polysomnography measures of sleep that may have contributed to the differences observed before and after CPAP. However, our recent analysis of EEG profiles on patients with OSA recorded in the sleep laboratory on two different nights showed remarkable intra-individual stability in NREM delta and sigma power [ 44 ]. We used a standardised computerised battery of performance tasks assessing cognitive domains known to be impaired in OSA [ 25 ] with demonstrated sensitivity to CPAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While no sex differences were noted for SWA in OSA, differences were found predictably across age groups with younger OSA patients having significantly higher relative SWA compared with elderly OSA patients (Lee et al, 2016; Munoz‐Torres et al, 2020). SWA in OSA also remained stable across time within individuals during an average time period of 3 months with no clinical or OSA severity changes (Poon et al, 2019). However, SWA might be affected by changes in disease severity over longer periods of time.…”
Section: Eeg Measures Of Sleep Microstructure In Osamentioning
confidence: 99%
“…Several studies have examined sleep spindles in the OSA population, as well as changes in spindle characteristics after OSA treatment. Spindles in NREM sleep were shown to be highly stable across nights in patients with OSA, at testing intervals ranging from 13 days up to 3 years (Poon et al, 2019). Early studies based on PSA and an automatic spindle detector showed that spindle density and spindle frequency were lower in middle‐aged patients with mild‐to‐moderate OSA compared with non‐OSA controls (Guilleminault et al, 2001; Himanen et al, 2003; Huupponen et al, 2003; Ondze et al, 2003).…”
Section: Eeg Measures Of Sleep Microstructure In Osamentioning
confidence: 99%